2018
DOI: 10.1080/15384101.2018.1467675
|View full text |Cite
|
Sign up to set email alerts
|

The long non-coding RNA LSINCT5 promotes malignancy in non-small cell lung cancer by stabilizing HMGA2

Abstract: Long non-coding RNAs (lncRNAs) can actively participate in tumorigenesis in various cancers. However, the involvement of lncRNA long stress induced non-coding transcripts 5 (LSINCT5) in non-small cell lung cancer (NSCLC) remains largely unknown. Here we showed a novel lncRNA signature in NSCLC through lncRNA profiling. Increased LSINCT5 expression positively correlates with malignant clinicopathological features and poor survival. LSINCT5 can promote migration and viability of various NSCLC cells in vitro and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 35 publications
3
20
0
Order By: Relevance
“…Subsequently, Silva et al [12] further found LSINCT5 expression levels were obviously increased in breast and ovarian cancer tissues and cell lines compared with their corresponding normal tissues and cell lines, respectively. Recently, LSINCT5 overexpression has been identified in lung cancer [13], hepatocellular carcinoma [14], bladder cancer [15], gastric cancer [16,17] and colorectal cancer [16]. In our study, we also found LSINCT5 expression was increased in osteosarcoma tissue samples and cell lines, which was similar to recent study reported by Kong et al [10].…”
Section: Discussionsupporting
confidence: 91%
“…Subsequently, Silva et al [12] further found LSINCT5 expression levels were obviously increased in breast and ovarian cancer tissues and cell lines compared with their corresponding normal tissues and cell lines, respectively. Recently, LSINCT5 overexpression has been identified in lung cancer [13], hepatocellular carcinoma [14], bladder cancer [15], gastric cancer [16,17] and colorectal cancer [16]. In our study, we also found LSINCT5 expression was increased in osteosarcoma tissue samples and cell lines, which was similar to recent study reported by Kong et al [10].…”
Section: Discussionsupporting
confidence: 91%
“…The low survival rate of OS is mainly due to the fact that patients are prone to focus metastasis. Previous studies have shown that LSINCT5 can inhibit the metastasis of lung cancer by regulating HMGA2, 24 while our research has found that LSINCT5 also has the function of inhibiting tumor cell metastasis in OS, which has indicated that LSINCT5 has the function of inhibiting tumor metastasis in various tumors. In order to further explore the mechanism of LSINCT5, we predicted the miR that LSINCT5 could bind to it.…”
Section: Discussionmentioning
confidence: 44%
“…In addition, there is a current lack of highly sensitive and specific markers for the diagnosis of early-stage LUAD. Recently, long non-coding RNAs (lncRNAs) have become novel and popular markers for detecting tumors in the bloodstream, which could allow for the dynamic monitoring of tumor cell invasion, activity and patient prognosis (Tian et al, 2018b; Zhao et al, 2018). In addition, lncRNAs have been found to exert multiple functional roles in lung cancer (Li et al, 2018; Qian et al, 2018; Yu et al, 2018; Zhang et al, 2018b).…”
Section: Introductionmentioning
confidence: 99%